STUDY LITERATURE THE CORRELATION BETWEEN STUDENT’S VOCABULARY MATERY AND SPEAKING SKILL - Ahmad Yanuar Syauki; Suhendra; Fathonah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Banten, 2022)
As we know that vocabulary is important component because it is one of element that linked the four skills of language. Vocabulary is list or collection of words and phrases usually alphabetically arranged and explained or define, it is one of most fundamental components of language. Without vocabulary mastery, nobody can communicate through language, whereas speaking is one way to express ideas, though a message orally, speaking ability is the goal from the study of language, speaking is one of the most important skills to be developed and enhanced as means of effective communication. Speaking skill is regarded one of the most difficult aspects of language learning. The objective of this research is to find out is there any significant correlation between students’ vovabulary mastery and speaking skill, and the method used in this researc is study literature, study literature is required in research whose sole purposes is to develop both theorical benefits aspect, and the aim of research is to finding a footing or foundation for obtaining and building a bassic for the theory of framework and estabilishing hypotheses so that researchers can understand the locatingof organized and than use variation of libraries in field.